Regulasi Perjanjian Perkawinan Pada UU No 1 Tahun 1974 dan Kompilasi Hukum Islam (Studi Maslahah Al-Ghazali) - Bahri, Saeful Muda; -, Suprihatin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
Marriage is a common sunnah and applies to all His creatures. Every prospective or marriedcouple certainly expects the marriage they want according to the guidance of religious law andapplicable law. However, not all marriages go smoothly as the purpose of the marriage, many thingsthat cause the end of a marriage including domestic violence, economics, infidelity and other factors.Therefore, the law is present to solve the phenomenon of marital problems that occur in society. Thusthe presence of the law is to realize the benefit, happiness, and discipline of the law. the presence of therule of law of marriage agreement to regulate the issue is contained in Law No. 1 of 1974 on Marriagecontained in Chapter V of the Marriage Covenant and on the Compilation of Islamic Law Chapter VIIof the Marriage Covenant. Research library research with the specificity of normative legal researchwith the approach of legislation and the benefit of al-Ghazali. The legal materials of this researchcome from primary, secondary, and tertiary legal materials, such as books, legal literature, legalliterature, civil law, as well as books and books discussing the benefits of marriage covenants. Fromthe results of the study, obtained maslahah Imam al-Ghazali seen in two aspects. First, the context ofthe existence of the rule of law concerning marriage agreements. Second, maslahah of the functionof the use of marriage covenants. In the benefit of both can be known that the Law No. 1 of 1974 isglobal or National contains emergency benefits on aspects of hifz al-din (maintaining religion) andhifz al-nafs (nurturing the soul) and the Compilation of Islamic Law that is specifically applicable tothe Islamic community in Indonesia contains the benefit of hajjyat in this case necessary for the benefitof the Islamic community in answering the question for the sake of the question of the rule of marriagelaw. While in the function of the use of the rule of law regarding marriage agreements in Law No. 1of 1974 and the Compilation of Islamic Law occupies the emergency benefit in maintaining religion,soul, reason, offspring, and property